Fun for the Whole Family - Smith, Jennifer E. ([Place of publication not identified] : Ballantine Books, 2025)
"The four Endicott siblings--Gemma, Connor, Roddy, and Jude--were once inseparable, a bond created by the absence of their dazzling, mercurial mother, who would return for a few weeks each summer to whisk them off on sprawling road trips around the country. Decades later, the unthinkable has happened: the Endicotts haven't spoken in years ... until an out-of-the-blue text arrives from Jude, now a famous actress, summoning them to a small town in North Dakota. They're each at a crossroads: Gemma, who put her own ambitions aside to raise the others, now isn't sure if she wants to be a mother herself; Connor, a celebrated novelist, is floundering after his recent divorce and suffering from an epic case of writer's block; and Roddy, at the tail end of a professional soccer career, is dangerously close to losing his future husband for the chance at one last season. Jude is the only Endicott who seems to have it all together--but appearances can be deceiving. As the weekend unfolds, and the siblings wrestle with their shared past and uncertain futures, they'll discover that Jude has been keeping three secrets ... each of which could change everything."--Provided by publisher.
new book 2025 spring.
Keywords: Family secrets; Domestic fiction; Life change events; Siblings